The Effect of Resistance Exercise to Prevent and Manage Sarcopenia - Hartono, Dicky; Christine, Angela; Eny, Anggraini; I Putu, Adiatmika Gede (Sport and Fitness Journal; Vol 11 No 3 (2023): Volume 11, No. 3, September 2023, 2024)
Sarcopenia is a loss of muscle mass and function because of the aging process. The goal of this literature review was to evaluate an resistance training efficacy on pre-sarcopenic body composition and strength in elderly. This literature review will investigate the effect of resistance training determined by body mass analysis in the sarcopenia patient. Google Scholar, ResearchGate, and Mendeley were used as the search engine. The keywords were strength training, resistance exercise & sarcopenia. The effect of resistance exercise on sarcopenia prevention were analyzed from 28.300 articles. Significant effect on sarcopenia proofed by body composition improvement. The depletion of lean body and total fat mass was analyzed by a mean of gram unit. An easy-to-use functional resistance exercise was effective to maintain functional strength and to gain muscle mass in pre-sarcopenia elderly patients.